2019
DOI: 10.3389/fpsyt.2019.00074
|View full text |Cite
|
Sign up to set email alerts
|

Sex Specific Changes in Tryptophan Breakdown Over a 6 Week Treatment Period

Abstract: Introduction: Despite the knowledge of sex differences concerning neurobiological parameters as well as clinical course of illness in individuals with mood disorders, the literature concerning tryptophan (Trp) breakdown, specific for women and men, is sparse to date. The current study aimed to evaluate sex differences in Trp, kynurenine (Kyn) and Kyn/Trp concentrations in general, as well as differences in changes of those concentrations over the course of a 6-week rehabilitation program in individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
3
11
0
Order By: Relevance
“…They found significantly decreased Trp levels in fatigued survivors. Kyn/Trp ratios and neopterin levels were higher in fatigued than in nonfatigued survivors with borderline significance, and the difference was more prominent in men survivors than in women survivors, a finding consistent with other studies showing that the Trp breakdown differs between men and women (Reininghaus et al, 2019). Future studies are needed to control for the effects of gender and cancer stage and to track the changes in Kyn pathway metabolites and symptoms among cancer survivors who have completed major cancer treatment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…They found significantly decreased Trp levels in fatigued survivors. Kyn/Trp ratios and neopterin levels were higher in fatigued than in nonfatigued survivors with borderline significance, and the difference was more prominent in men survivors than in women survivors, a finding consistent with other studies showing that the Trp breakdown differs between men and women (Reininghaus et al, 2019). Future studies are needed to control for the effects of gender and cancer stage and to track the changes in Kyn pathway metabolites and symptoms among cancer survivors who have completed major cancer treatment.…”
Section: Discussionsupporting
confidence: 90%
“…Second, some studies did not control for the influence of confounding factors, including age, sex, cancer stage, and pharmacologic agents. Notably, some antidepressants can modulate Trp and Kyn metabolism (Eskelund et al, 2017), and sex is associated with different types of changes in Kyn/Trp ratios and neopterin (Reininghaus et al, 2019). These sources of variability might have impacted our findings of associations between metabolites and psychoneurological symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Kynurenine is associated with inflammation processes as well as aging [ 26 ]. Additionally, sex-specific differences have been reported for increased concentrations of kynurenine mainly in male individuals with affective disorders over a six-week psychiatric rehabilitation program [ 27 ]. Psychiatry research is particularly interested in the pathways of monoamine synthesis interplay with the inflammatory homeostasis catabolism and their link to neuropsychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Hestad et al ( 2017 ) measured tryptophan concentrations, in addition to kynurenine and the ratio between kynurenine and tryptophan, in a sample of individuals with and without depression, and found that women had lower levels of both serum and cerebrospinal fluid tryptophan compared to men, irrespective of their diagnostic status. Similarly, another study on 426 individuals with lifetime affective disorder reported significant differences between men and women regarding the changes in tryptophan, kynurenine and their ratio over a 6-week period, reporting lower serum levels in women (Reininghaus et al 2019 ). Second, reactive aggression is a well-documented construct which has been shown to vary, at least overtly, between genders (e.g.…”
Section: Discussionmentioning
confidence: 97%